2023
DOI: 10.3390/nu15030635
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Resveratrol Butyrate Monoester Supplement Improves Hypertension and Kidney Dysfunction in a Young Rat Chronic Kidney Disease Model

Abstract: Chronic kidney disease (CKD) remains a public health problem. Certain dietary supplements can assist in the prevention of CKD progression. In this regard, resveratrol is a polyphenol and has a potential therapeutic role in alleviating CKD. We previously utilized butyrate in order to improve the bioavailability of resveratrol via esterification and generated a resveratrol butyrate monoester (RBM). In this study, the hypothesis that RBM supplementation is able to protect against kidney dysfunction and hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The current study demonstrated that the relative abundance of Monoglobus significantly decreased in PC treatment and was positively correlated with the level of proinflammatory factors. A previous study showed that Monoglobus might have a protective effect on chronic kidney disease [70]. Therefore, the specific effects of Monoglobus on the host under the disease state requires further clarification.…”
Section: Discussionmentioning
confidence: 96%
“…The current study demonstrated that the relative abundance of Monoglobus significantly decreased in PC treatment and was positively correlated with the level of proinflammatory factors. A previous study showed that Monoglobus might have a protective effect on chronic kidney disease [70]. Therefore, the specific effects of Monoglobus on the host under the disease state requires further clarification.…”
Section: Discussionmentioning
confidence: 96%
“…Various adenine-treatment protocols, using concentrations and durations-different from that in the original protocol established by Yokozawa et al 18) -have since been used, leading to variations in the induced renal dysfunction. [22][23][24] Here, we used rats orally treated with adenine at 600 mg/kg for 10 d, which exhibited stable kidney dysfunction, as established by previous reports. 16,17) Furthermore, we confirmed renal dysfunction because serum creatinine and BUN were elevated in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies published by our team also successfully esterified RSV with butyric acid-forming RBEs, which exhibited more excellent hydrogen peroxide scavenging activity than RSV (Tain et al, 2021) while effectively inhibiting fatty acidinduced lipid accumulation in HepG2 cells (Tain et al, 2020). The efficacy of resveratrol in preventing hypertension and kidney damage in young rats with chronic kidney disease is comparable to that of resveratrol, although it is dose-independent (Tain et al, 2023). RBEs have been shown to have preventative effects in pregnant and lactating rats supplemented with drinking water, protecting offspring from hypertension due to maternal di-2-ethyl hexyl phthalate (DEHP) exposure.…”
mentioning
confidence: 82%
“…RBEs were synthesized and isolated following the approach of Shih et al (2021) and Tain et al (2023). Briefly, trans-RSV (91.3 g, 0.2 mol) was mixed with butyric acid (80 g, 0.22 mol) in 1 L of anhydrous tetrahydrofuran (THF), then N-ethyl-N 0 -(3-dimethylaminopropyl) carbodiimide (EDC; 68.4 g, 0.22 mol) and 4-dimethylaminopyridine (DMAP; 53.8 g, 0.11 mol) were added, followed with nitrogen stirring at room temperature for 48 h. The reaction process was protected from light throughout, while the flasks were wrapped with aluminum foil.…”
Section: Synthesis and The Isolation Of Rbesmentioning
confidence: 99%
See 1 more Smart Citation